Detektor Sensor Sht11 Sebagai Monitoring Suhu Dan Kelembaban Ruang Berbasis Mikrokontroler Atmega16a Di-Smart Avr System - Agus Herawan; Ahmad Fauzi (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
In a room, whether it is an open or closed room, there are various kinds of circumstances or conditions. The condition affects the value contained relativity weather environment around where we are. As well as the normal condition of the human body temperature that ranges between 36.5°C upto 37.5°C, so it should always be monitored and maintained the normal condition, if not then there is an undesirable state such as fever. Normal human body temperature conditions can be determined by using a measuring instrument such as a thermometer. In this paper designed a series of applications used to monitoring the amount of temperature and humidity of an opened and closed rooms. Results from research using SHT11 sensor shows the magnitude of temperature and humidity performed in close room for 12 hours with an average yield of ambient temperature and humidity chamber are -8.79°C and 84.1%.